2007
DOI: 10.1159/000099190
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Pathways of the Calcium-Sensing Receptor on Acid Secretion in Freshly Isolated Human Gastric Glands

Abstract: Gastric acid secretion is not only stimulated via the classical known neuronal and hormonal pathways but also by the Ca2+-Sensing Receptor (CaSR) located at the basolateral membrane of the acid-secretory gastric parietal cell. Stimulation of CaSR with divalent cations or the potent agonist Gd3+ leads to activation of the H+/K+-ATPase and subsequently to gastric acid secretion. Here we investigated the intracellular mechanism(s) mediating the effects of the CaSR on H<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…Moreover, we can speculate that calcium transients remained active in presence of PKC modulators because they are triggered by the PLC-IP 3 pathway, upstream PKC (Young & Rozengurt 2002). Studies on CASR and PKC isoforms demonstrated that both conventional and novel PKC isoforms are activated by [Ca 2C ] o increases (Remy et al 2007) and PKC-specific inhibitors did not completely abolish ERK1/2 phosphorylation (Sakwe et al 2004). Novel PKCs (d, 3, h, and q) are activated by [Ca 2C ] i and diacyl glycerol, whereas conventional PKCs (a, b, and g) are activated only by [Ca 2C ] i , so we can speculate that the oscillatory response of CASR 990G could require only one PKC group (Oancea & Meyer 1998, Young et al 2002.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, we can speculate that calcium transients remained active in presence of PKC modulators because they are triggered by the PLC-IP 3 pathway, upstream PKC (Young & Rozengurt 2002). Studies on CASR and PKC isoforms demonstrated that both conventional and novel PKC isoforms are activated by [Ca 2C ] o increases (Remy et al 2007) and PKC-specific inhibitors did not completely abolish ERK1/2 phosphorylation (Sakwe et al 2004). Novel PKCs (d, 3, h, and q) are activated by [Ca 2C ] i and diacyl glycerol, whereas conventional PKCs (a, b, and g) are activated only by [Ca 2C ] i , so we can speculate that the oscillatory response of CASR 990G could require only one PKC group (Oancea & Meyer 1998, Young et al 2002.…”
Section: Discussionmentioning
confidence: 90%
“…Vitamin D deficiency may limit mobility in community dwelling older adults [74], which may impact on instrumental activity of daily life (IADL)-score. In theory the influence on the prevalence of peptic ulcers may be secondary to stimulation of intestinal Ca 2+ absorption with subsequent increase of extracellular Ca 2+ and stimulation of gastric H + secretion by the Ca 2+ sensing receptor [75,76]. The known influence of VDR on the immune response [6,7,8] may have contributed to or even accounted for the impact of the VDR rs2228570 polymorphism on allergy.…”
Section: Discussionmentioning
confidence: 99%
“…The main function of chief and parietal cells is the secretion of pepsinogens and gastric acid, respectively. Both secretion processes are coupled and mediated by the intracellular Ca 2+ signalling (Hou and Schubert 2006;Remy et al 2007;Kimura et al 2001;Gritti et al 2000). The localisation of NUCB2 in the secretory granules of chief cells and its loss in atrophic glands suggests a role in the secretion processes by establishing an agonistreleasable Ca 2+ store in ER or Golgi apparatus, signalling via heterotrimeric Gα proteins and/or mediating the exocytosis of the secretory granules.…”
Section: Discussionmentioning
confidence: 99%